Perumahan : pembangunan, pengurusan dan pemasaran estet - Ibrahim Wahab; Azlizan Talib; Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2017)
Housing development, management and marketing of estates in Malaysia.
Includes bibliographical references (pages 173-180) and index.
In Malay.
Keywords: Housing development -- Malaysia